Generation of Mixed-Driving Multi-Bit Flip-Flops for Power Optimization - Liu, Meng-Yun; Lai, Yu-Cheng; Mak, Wai-Kei; Wang, Ting-Chi (2022 IEEE/ACM International Conference On Computer Aided Design (ICCAD), 2022)
Multi-bit flip-flops (MBFFs) are often used to reduce the number of clock sinks, resulting in a low-power design. A traditional MBFF is composed of individual FFs of uniform driving strength. However, if some but not all of the bits of an MBFF violate timing constraints, the MBFF has to be sized up or decomposed into smaller bit-width combinations to satisfy timing, which reduces the power saving. In this paper, we present a new MBFF generation approach considering mixed-driving MBFFs whose certain bits have a higher driving strength than the other bits. To maximize the FF merging rate (and hence to minimize the final amount of clock sinks), our approach will first perform aggressive FF merging subject to timing constraints. Our merging is aggressive in the sense that we are willing to possibly oversize some FFs and allow the presence of empty bits in an MBFF to merge FFs into MBFFs of uniform driving strengths as much as possible. The oversized individual FFs of an MBFF will be later downsized subject to timing constraints by our approach, which results in a mixed-driving MBFF. Our MBFF generation approach has been combined with a commercial place and route tool, and our experimental results show the superiority of our approach over a prior work that considers uniform-driving MBFFs only in terms of the clock sink count, the FF power, the clock buffer count, and the routed clock wirelength.